READY TEACHERS’ READINESS FOR USE EMPATHIES AS CONDITIONS OF DEVELOPMENTAL INFLUENCE - Kyrychok, I.I. (Pedagogy of Higher and Secondary Education, 2022)
The author considers the problem of empathy as a developmental means of interaction in the interpersonal relations between the teacher and pupils, analyzes the readiness of future teacher to the use of empathy influence on the school-children. Attentions is paid to the socialpsychological training of the development of empathy as a condition of the teacher’s professional suitability.